Aperiodic task Scheduling Algorithms for Multiprocessor systems in Real Time environment (International Journal of Engineering and Computer Science, 2015)
Multiprocessor systems contains multiple processors either homogeneous or heterogeneous, scheduling tasks for such system is very critical and hence scheduling protocol should be followed for optimality.Scheduling algorithms gives the scheduler a set of protocols to manage the real time systems. In this paper we present an overview of aperiodic task scheduling algorithms servers for real-time systems on multiprocessor systems and method is proposed for the aperiodic task having communication delay which can be scheduled using a Genetic Algorithm (GA)